PHARMACOKINETICS OF AVERSECTIN С1 AND PRAZIQUANTEL IN DOG BLOOD AFTER A SINGLE SUBCUTANEOUS INJECTION OF AVERTEL - V. B. Yastreb; T. S. Novik; V. A. Drinyaev; S. I. Chukina; S. V. Avchuk; V. G. Ter–Simonyan; A. A. Litvin (Российский паразитологический журнал)
Objective of research:  study of pharmacokinetics of Aversectin С1 and Praziquantel in blood plasma of dogs after a single subcutaneous injection of Avertel. Materials and methods:  experiments were conducted on 3 dogs which received Avertel shots in the neck area at a therapeutic dose 0,5 mg/kg of Aversectin C1 and 5 mg/kg of Praziquantel. Blood was collected from the forearm vein into heparin test-tubes at 0; 0,5; 1; 2; 3; 6; 9; 12; 24; 36; 48 and 72 hr. Analysis of dog blood for  Aversectin  C1  (according  to  the total Avermectins  В1аand  В2а)  was performed by the method of high-performance liquid chromatography with fluorescence detection;  the sensitivity of the method was  0,001  mg/l.    Praziquantel was identified by the same method using the ultraviolet detection. For evaluation of the pharmacokinetic properties, the model-independent analysis «M-IND» was applied which enables to perform the primary processing of data «drug concentration  – time» and calculate the system parameters of drugs by the method of moments. Results and discussion: Aversectin   С1 was detected in blood 0,5hr after Avertel injection. Further,  the drug  concentration in blood  has increased; at 24th  hour,  the highest level of drug was determined; then the drug concentration went down. Aversectine С1 was also found in dog blood 72 hours after  the Avertel injection.  Praziquantel was identified 0,5hr  after its  injection, and 1hr  later its highest concentration  has been  registered. 72 hours later the drug wasn’t found in dog blood.  The highest concentration of Aversectin С1 in blood was 13,4 ng/ml, and it was being eliminated 12 times slower  than Praziquantel.  The elimination half-life of Aversectin С1 was 100,1 hrs. and the average residence time of the drug in the body -153,08 hrs.